PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SDN 15 PINGGIR KECAMATAN PINGGIR KABUPATEN BENGKALIS - Pandu Paprika; Armis Armis; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This research is the action research that aims to improve the students learning outcomes of the fifth grade of SDN 15 Pinggir. This research was conducted in the first semester of the academic year 2013/2014. The subjects were the fifth grade class of SDN 15 Pinggir. The total students is 35 people. This study was conducted in two cycles, by prepare three instrument, there are silabus, RPP, and LKS. Collecting activity data by using observation sheet and daily test. Analysis of the data used is describes the activities of teacher and students, analysis of learning outcomes and succesful measurements. From analysis research, increasing the number of students who achieve at UH KKM in every end of each cycle compared to the number of the students who achieve a schore of KKM on basic score. The result of this study explanations that through the application of cooperative learning model Numbered Heads Together (NHT) can improve the students learning outcomes of the fifth grade of SDN 15 Pinggir.Keywords: Classroom Action Research (CAR). Cooperative Learning Model Type Numbered Heads Together (NHT). Mathematics Learning Outcomes.